2012
DOI: 10.1177/0891988712445088
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Five-Word Test for the Evaluation of Verbal Episodic Memory and Dementia in a Memory Clinic Setting

Abstract: The FWT is a valid test of verbal episodic memory. It is useful to discriminate dementia especially AD from isolated subjective complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…We administered FWT and the short story test to patients suffering from MCI or dementia due to AD [19, 20] and to a control group: our findings confirm literature data [16, 17, 22] demonstrating the effectiveness of FWT as a tool in identifying organic disorders of memory encoding and in distinguishing AD patients from controls. The distribution of subjects by age, gender, and education level was different among the diagnostic subgroups, reflecting the day-to-day work in a memory clinic with a heterogeneous, unselected population.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…We administered FWT and the short story test to patients suffering from MCI or dementia due to AD [19, 20] and to a control group: our findings confirm literature data [16, 17, 22] demonstrating the effectiveness of FWT as a tool in identifying organic disorders of memory encoding and in distinguishing AD patients from controls. The distribution of subjects by age, gender, and education level was different among the diagnostic subgroups, reflecting the day-to-day work in a memory clinic with a heterogeneous, unselected population.…”
Section: Discussionsupporting
confidence: 77%
“…Considering that data for standardized raw score adjustment are not available for the FWT [16, 17, 22, 23], the multivariate logistic regression analysis showed that the TRS remained discriminant even when taking into account age, education level, and sex distribution, both in MCI (95% CI: 0.14–0.45; p < 0.001) and in AD patients (95% CI: 0.004–0.18; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations